1994
DOI: 10.1093/jmedent/31.5.711
|View full text |Cite
|
Sign up to set email alerts
|

Eastern Equine Eneephalomyelitis Virus in Relation to the Avian Community of a Coastal Cedar Swamp

Abstract: Eastern equine encephalomyelitis virus (EEEV) is perpetuated in eastern North America in a mosquito-wild bird maintenance cycle that involves Culiseta melanura (Coquillett) as the principal enzootic vector and passerine birds as the primary amplifying hosts. We examined the role of birds in the EEEV cycle at a site in southern New Jersey where EEEV cycles annually at high levels. Birds and mosquitoes were sampled during three epiornitics and one season of limited virus activity. We examined antibody prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
94
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 16 publications
4
94
0
Order By: Relevance
“…6,7 Historically in the United States, large studies along the Mississippi and Atlantic flyways failed to document the introduction of encephalitis viruses by northbound migrants. [8][9][10][11] In agreement, genetic studies have shown marked separation between North and South American strains of arboviruses, such as eastern equine encephalomyelitis (EEEV), 12 western equine encephalomyelitis (WEEV), 13,14 and St. Louis encephalitis (SLEV) 15,16 viruses, suggesting limited genetic exchange. Temporal studies in California have shown intermittent genotype change among WEEV and SLEV isolates, [17][18][19] indicating possible introduction and replacement events.…”
Section: Introductionmentioning
confidence: 84%
“…6,7 Historically in the United States, large studies along the Mississippi and Atlantic flyways failed to document the introduction of encephalitis viruses by northbound migrants. [8][9][10][11] In agreement, genetic studies have shown marked separation between North and South American strains of arboviruses, such as eastern equine encephalomyelitis (EEEV), 12 western equine encephalomyelitis (WEEV), 13,14 and St. Louis encephalitis (SLEV) 15,16 viruses, suggesting limited genetic exchange. Temporal studies in California have shown intermittent genotype change among WEEV and SLEV isolates, [17][18][19] indicating possible introduction and replacement events.…”
Section: Introductionmentioning
confidence: 84%
“…One potential overwintering mechanism is latent or chronic infection of wild birds. In such a scenario, springtime viral recrudescence might reinitiate the transmission cycle each new season (21,22). However, the results of a serologic survey of wild birds in upstate New York during 1986-1990 failed to support this notion, showing no consistent evidence for the current or recent infection of after-hatch year birds with EEEV early in the transmission season (23).…”
Section: Discussionmentioning
confidence: 99%
“…Eastern equine encephalitis virus was demonstrated to survive as a persistent infection of resident birds in southern New Jersey. 26 Reeves 4 made two isolations of WEE virus from the blood of white-crowned sparrows collected in the winter in Kern County, and laboratory studies 4 demonstrated that passerine birds may become chronically infected; however, efforts to infect mosquitoes by feeding on these same birds were unsuccessful. Alternatively, virus may overwinter in the adult mosquito.…”
Section: Discussionmentioning
confidence: 99%